Prophetic Politics: Mohammed Arkoun's Rethinking of Islam in Contemporary Politics - Utomo, Wahyu Wiji (Jurnal Review Politik, 2024)
This article examines Mohammed Arkoun's concept of "Prophetic Politics" within Rethinking Islam to address the challenges of modernity and secularization in contemporary politics. Using a qualitative literary method that involves in-depth contextual analysis of sacred texts, Arkoun's thought is positioned as a bridge between Islamic tradition and modern political demands. The study explores how prophetic values can provide an ethical and moral framework for policy-making and governance. Using an Applied Islamic Studies approach, the article critiques orthodox interpretations and advocates for a dynamic, tolerant, and inclusive political model. Findings emphasize the integration of spirituality in modern governance, ensuring Islam's relevance without losing its essential values. The study concludes that Arkoun's Rethin-KingRethin-KingRethin KingRethin King Islam offers valuable perspectives on the role of religion in evolving politics.